The Effect of using Problem Based Learning (PBL) on Students’ Listening Ability of Indonesian Academy of Secretary and Management (ASMI) Citra Nusantara Banjarmasin - Tiara Mardina; Misrita Misrita; Bahing Bahing (Universitas Muhammadiyah Enrekang, 2022)
This paper aims at finding out whether or not Problem Based Learning (PBL) can improve students’ listening ability. This research was experimental research, which aims to find out the effect of using Problem Based Learning (PBL) model for improving students’ listening ability. The population of this research were the sixth semester students of Indonesian Academy of Secertary and Management Indonesia (ASMI) Citra Nusantara Banjarmasin. Sample are students mayoring Financial management 1 as experimental group and students mayoring Financial Management 2 as control group. It is obtained by using purposive sampling. Experimental group was taught by using Problem Based Learning (PBL) Model consist of 22 students. While control group was taught by using conventional model consist of 23 students. The instrument of this research was TOEIC Listening Comprehension Test. Problem Based Learning (PBL) model was more effective to improve students’ listening ability at Indonesian Academy of Secertary and Management Indonesia (ASMI) Citra Nusantara Banjarmasin than conventional model. It was indicated by the result of independent sample t-test, it was found the sig. (2 tailed) value was 0.000 < 0.05. It meant that, H0 was rejected, and Ha was accepted. Furthermore, it can be interpreted that there was significance difference on students’ listening ability between experimental group and the control group. In group statistics table said that the mean of experimental group was 275.91. It was higher than the mean of control group 194.57. It could be stated that Problem Based Learning (PBL) model in teaching listening could improve the students' listening ability better than the conventional model.